2014
DOI: 10.1248/bpb.b13-00695
|View full text |Cite
|
Sign up to set email alerts
|

(2<i>S</i>)-2′-Methoxykurarinone Inhibits Osteoclastogenesis and Bone Resorption through Down-Regulation of RANKL Signaling

Abstract: (2S)-2′-Methoxykurarinone (MK), a compound isolated from the roots of Sophora flavescens, has various physiological properties, such as anti-inflammatory, antipyretic, antidiabetic, and antineoplastic effects. However, the effect of S. flavescens-derived MK on osteoclastogenesis remains unknown. Therefore, we examined the effect and mechanism of action of MK on receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclast differentiation and bone resorption. MK inhibited osteoclast differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, inhibition of RANKL and IL-1-induced osteoclast differentiation, through the inhibition of Akt phosphorylation, has also been reported following treatment with (2S)-2′-Methoxykurarinone prenylflavonoid (Kim et al 2014 ).…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, inhibition of RANKL and IL-1-induced osteoclast differentiation, through the inhibition of Akt phosphorylation, has also been reported following treatment with (2S)-2′-Methoxykurarinone prenylflavonoid (Kim et al 2014 ).…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…Several works report the anti-inflammatory effects of polyphenols, being exerted through targeting MAPKs pathway (Fig. 5 ): EGCG plays a role against inflammatory cytokines, which favor bone resorption, by inhibiting, at a dose of 30 μM, endothelin1 and platelet-derived growth factor BB-induced IL-6 synthesis, through diminishing the phosphorylation levels of MEK1/2 and Raf-1 at a point upstream of ERK1/2 MAPK (Tokuda et al 2007a ) and through downregulating the stress-activated protein kinase (SAPK)/JNK pathway (Takai et al 2008 ); (2S)-2′-Methoxykurarinone, a compound isolated from the root of Sophora flavescens , inhibits, at the dose of 20 μM, IL-1-induced differentiation of osteoclasts through the inhibition of p38 and JNK phosphorylation (Kim et al 2014 ), while icariin, at nM concentrations, decreases PGE 2 production by suppressing activation of p38 and JNK pathways (Hsieh et al 2011 ).…”
Section: Mapks Cascadementioning
confidence: 99%
“…13) Accumulating lines of evidence suggest that several natural compounds may have potential anabolic effects on bone. 14,15) Carvacrol (5-isopropyl-2-methylphenol), is a monoterpenic phenol found in oregano and thyme. 16) Essential oils containing carvacrol have been widely used in various traditional medicines.…”
mentioning
confidence: 99%
“…Various medicinal compounds prepared from crude plant extracts that act on osteoclast differentiation and functions have been reported to have therapeutic benefits with few side effects in the treatment or prevention of bone diseases. To identify novel compounds that can function as antiresorptive agents, several natural compounds were screened by analyzing TRAP staining. Harpagoside (HAR, Figure A) is an iridoid glycoside isolated from Harpagophytum procumbens (devil’s claw) that has been used to treat pain, arthritis, fever, ulcers, and boils in Southern Africa and has been described as an anti-inflammatory and analgesic agent. , We found that HAR suppressed RANKL-mediated osteoclast differentiation from bone marrow macrophages (BMMs).…”
mentioning
confidence: 99%